(untitled) (Research, Society and Development, 2021)
This work presents the intervention performed in the State School Francisco Araujo Barreto, in the municipality of Jaciara - MT, with the application of astronomy content in Science discipline with the students of 6th and 9th grade of elementary school. The theme addresses the astronomy content theoretically and practices in order to lead to learning that is meaningful. For 5 classes the topics of basics of Astronomy were addressed with lectures and practices. Strategies to facilitate the teaching-learning were as follows at the beginning of the first two classes were applied a questionnaire to collect data on students’ prior knowledge, the practical classes were applied so that all students produce their material to the growth and enrichment of knowledge, finally the students were taken to the municipal stadium to meet a planetarium, expository and theoretically the class had an importance of great importance to students, at the end of the 5 classes completed a questionnaire reaching the expected goal. The achieved result showed that theoretical as aulas and de astronomy practices were positive, motivating students to participate in classes and activities, and also enabling meaningful learning.